Analysis Of Nutrition Levels Of Nitrogen, Phosphore, Potassium, C-Organic And Ph In Rice Soil In Dumoga District, Bolaang Mongondow Regency - Lintje Theffie Karamoy (Jurnal Agroekoteknologi Terapan, 2022)
This research uses survey method with composite soil sampling technique. Soil samples were analyzed qualitatively by PUTS and quantitative soil analysis using soil analysis methods in the laboratory, namely N Keldjal method, P Bray K Sepetrometer, C-organic Walkey and Black and pH using a pH meter. This research was conducted in Southeast Dumoga, Bolaang Mongondow Regency for the point of soil sampling and soil analysis was carried out at the Chemistry and Soil Fertility Laboratory, Faculty of Agriculture, Unsrat Manado for 8 months. The results showed that the total N content at the time of processing was classified as moderate, after one month of planting and after harvesting was classified as low. The C-Organic content at the time of processing was classified as moderate, after one month of planting and after harvesting it was classified as low. The available P content at the time of processing was low, after one month of planting and after harvesting it was classified as very low. The K content available at the time of processing was classified as moderate, after one month of planting and after harvesting was classified as low. Soil pH at the time of tillage, after one month of planting and after harvesting is classified as slightly acidic and after harvesting the pH tends to decrease. Further research is needed on the available phosphorus content, organic c-organic and the pH of the paddy soil at each research location starting to be ready for planting, when the plants are 1 month old and at harvest time in each planting period. Keywords: Nutrient Content, Rice Fields, PUTS. Abstrak Penelitian ini mengunakan metode survey dengan teknik pengambilan sampel tanah komposit. sampel tanah dianalisis secara kualitatif dengan PUTS dan analisa tanah secara kuantitatif menggunakan metode analisa tanah di laboratorium yaitu N metode Keldjal, P Bray K Sepetrometer, C-organik Walkey and Black dan pH menggunakan pH meter. Penelitian ini dilaksanakan Dumoga Tenggara Kabupaten Bolaang Mongondow untuk titik pengambilan sampel tanah dan analisis tanah dilaksanakan di laboratorium Kimia dan Kesuburan Tanah Fakultas Pertanian Unsrat Manado selama 8 bulan. Hasil penelitian didapatkan bahwa Kandungan N total pada saat olah tergolong sedang, setelah satu bulan tanam dan setelah panen tergolong rendah. Kandungan C-Organik pada saat olah tergolong sedang, setelah satu bulan tanam dan setelah panen tergolong rendah. Kandungan P tersedia pada saat olah tergolong rendah, setelah satu bulan tanam dan setelah panen tergolong Sangat rendah. Kandungan K tersedia pada saat olah tergolong sedang, setelah satu bulan tanam dan setelah panen tergolong rendah. pH tanah pada saat olah, setelah satu bulan tanam dan setelah panen tergolong agak masam dan setelah panen pH cenderung turun. Perlu penelitian lanjut mengenai kandungan fosfor tersedia, c-organik dan pH tanah sawah pada setiap lokasi penelitian mulai siap ditanami, saat tanaman berumur 1 bulan dan saat panen dalam setiap periode tanam. Kata Kunci: Kadar Hara, Tanah Sawah, PUTS